Whose streets? Justice in transport decarbonization and gender - Vera Huwe (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2021)
This paper develops the justice implications of gendered power relations for transport decarbonization. I build on the need satisfier escalation framework by Mattioli (2016) and Brand-Correa et al. (2020) and its account of justice as equality in need satiation. I show that gendered power relations manifest at the level of the provisioning system as a profound gendered division of labor and androcentric biases in the built environment. Based on the German travel survey Mobilität in Deutschland (2017), I document how gendered arrangements in the provisioning system reverberate as gendered inequalities in car access, travel behavior and trip purpose, yet significantly intersect with household income and migration biography. Normatively, I argue that an account of justice recognizant of gendered power relations extends justice to inputs for and conversion rates faced in need satisfaction processes. Building on Susan Okin (1989), I establish that justice additionally requires (i) the intra-household division of labor for need satisfaction to be chosen freely and (ii) equality of opportunity to satiate needs. Androcentric biases in the built environment create gendered conversion rates and constrain equality of opportunity. Consequently, transport decarbonization policy needs to equalize conversion rates for care relative to paid employment when de-escalating carbon intensity to be just.
Keywords: 330; Transport; Human Needs; Climate Change; Gender Division of Labor; Urban Planning; Gender Justice